A tennis field test to objectively measure the hitting accuracy based on an Excel spreadsheet: Practical guidelines and applications - Delgado-García, G.; Vanrenterghem, J.; Courel-Ibanez, J.; Ruiz-Malagon, E. J.; Ruiz-Alias, S.; Soto-Hermoso, V. M. (International Journal of Racket Sports Science, 2019)
Stroke accuracy is highly related with tennis performance and has traditionally been quantified using general areasof scoring. Hence there is a need to develop methods that allow accuracy to be measured with higher resolution. The aim of the work is to develop a field test and an Excel spreadsheet associated that allows to evaluate the accuracy of the strokes with a resolution up to centimetres and to study how shots landings are distributed. The test consists of 4 series of 20 groundstrokes performed in the down the line or cross-court direction (this is modifiable). The 2D coordinates of bounce of the ball is recorded with a camera, digitalized using a specialized software and introduced in the Excel spreadsheet. Then it computes a series of parameters that describe the 95% confidence ellipse of the shot landing on the court. A real example of the test outcomes of two advanced players -performing forehands and backhands down the line-is shown. Consistent with previous literature both players obtained a better accuracy in the mediolateral direction than in the longitudinal direction and ellipses were oriented almost parallel to the sideline (ellipse tilts were below 12 degrees in all cases). Ellipse area was considerably greater for the backhand than for the forehand in player two (38.8 vs. 55.5 m2) but not in player one (51.5 vs. 50.8 m2). Finally, the centre location of the ellipse in the longitudinal axis was positive in all cases (near 200 cm) which suggest that both players preferred to make short shots rather than send the ball out of the limits of the baseline. We conclude that this methodology can be used by researchers that want to assess accuracy with high resolution and by coaches that want to evaluate -with high sensibility-the player progression after a training program.